2022
DOI: 10.3389/fmed.2022.839475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neutrophil Function in Granulocyte Concentrates From Prednisone- and G-CSF-Treated Donors: Effect of Stimulant, Leukapheresis and Storage

Abstract: Transfusion of granulocyte concentrates (GC) is an alternative therapy for neutropenic patients with life-threatening infections. While neutrophils are the main source of antimicrobial activity, only neutrophil numbers are used to certify GCs. The objective of this study was thus to functionally characterize neutrophils in GCs prepared by leukapheresis from G-CSF-stimulated donors and compare to the less characterized prednisone GCs. GCs prepared from healthy donors stimulated with prednisone and then G-CSF af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A total unit volume between 200 and 300 mL was observed in 95.1% of units ( n = 196), and RBC volume was kept below 30 mL in 97.6% of units ( n = 201). Increased WBC counts in donors, such as those described in this study, are associated with improved collection efficiency and decreased red cell contamination, possibly due to better interface generation between the WBCs and RBCs when the WBC count is high 8,9 . Because a subset of pre‐GCSF donors had collections performed using the Cobe Spectra, differences in apheresis machine efficiencies may have also contributed to these findings.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A total unit volume between 200 and 300 mL was observed in 95.1% of units ( n = 196), and RBC volume was kept below 30 mL in 97.6% of units ( n = 201). Increased WBC counts in donors, such as those described in this study, are associated with improved collection efficiency and decreased red cell contamination, possibly due to better interface generation between the WBCs and RBCs when the WBC count is high 8,9 . Because a subset of pre‐GCSF donors had collections performed using the Cobe Spectra, differences in apheresis machine efficiencies may have also contributed to these findings.…”
Section: Discussionmentioning
confidence: 67%
“…Increased WBC counts in donors, such as those described in this study, are associated with improved collection efficiency and decreased red cell contamination, possibly due to better interface generation between the WBCs and RBCs when the WBC count is high. 8,9 Because a subset F I G U R E 3 Mean (M), standard deviation (STD), medians, and interquartile ranges for unit ANC, total volume, platelet count, hematocrit, RBC volume, and donor pre-donation WBC count before (pre) and after (post) implementation of G-CSF donor stimulation. Percentage of units with ANC > 4.0 Â 10 10 following implementation of G-CSF donor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Immature peripheral blood neutrophils are reported to have reduced oxidative burst, impaired capacity to kill C. albicans and increased cytokine production to toll-like receptor (TLR) agonists [28][29][30]. We compared effector responses in cultured neutrophils and steady state native neutrophils isolated from peripheral blood, to explore any possible functional differences.…”
Section: Functional Comparison Of Cultured and Native Neutrophilsmentioning
confidence: 99%
“…GCSF administration is sufficient to mobilise immature neutrophils into the circulation; this was demonstrated in GCSF-treated allogeneic stem cell donors (GCSF-D) [28]. Importantly, these studies suggested functional differences between control and GCSF-D neutrophils, including elevated production of proinflammatory cytokines, reduced motility and capacity to produce ROS, as well as reduced ability to suppress the fungal pathogen Candida albicans (C. albicans) [19,[28][29][30].…”
Section: Introductionmentioning
confidence: 96%
“…GCSF administration is sufficient to mobilise immature neutrophils into the circulation; this was demonstrated in GCSF-treated allogeneic stem cell donors (GCSF-D) [27]. Importantly, these studies suggested functional differences between control and GCSF-D neutrophils, including elevated production of proinflammatory cytokines, reduced motility and capacity to produce ROS, as well as reduced ability to suppress the fungal pathogen Candida albicans (C. albicans) [18,[27][28][29]. These functional differences define a new appreciation for neutrophil heterogeneity or 'neutrophil states', breaking the mould of the terminally differentiated, uniform cells, which neutrophils have long been described as.…”
Section: Introductionmentioning
confidence: 97%